The Application of the International Emergency Economic Powers Act in the U.S.-China Trade War: Can A President Order U.S. Companies Out of China - Rita Liu (Washington University Global Studies Law Review, 2021)
This note discusses the legal framework of IEEPA and whether IEEPA gives the U.S. President the authority to order U.S. companies to stop business in China. First, this note explains the legal framework, the previous applications of IEEPA, and the economic background of President Trump's order. Second, this note focuses on the theoretical application of IEEPA and its limits. Finally, this note predicts the legal practicability and economic impact for the President to apply IEEPA to justify his U.S.-China trade war policy.